THE ROLE OF LABOR SERVICES IN EFFORTS TO REDUCE THE RATE OF OPEN UNEMPLOYMENT IN THE CITY OF SUKABUMI - Dharmawan, Randi Perdian; Nur, Tuah; Meigawati, Dine (DIA: Jurnal Administrasi Publik, 2025)
This study aims to examine the role of the Sukabumi City Manpower Office in reducing the open unemployment rate. Decent work is a right of every citizen as stated in Article 27 Paragraph 2 of the 1945 Constitution of the Republic of Indonesia. The government and local governments are responsible for creating jobs to absorb as much labor as possible and ensuring fair and satisfactory treatment for the population. The research method used is a literature study and secondary data analysis from the Central Statistics Agency (BPS). The results of the study indicate that despite government efforts to create jobs, the unemployment rate in Sukabumi City remains high. In 2022, the number of underemployed or unemployed workers reached 46.29 million people. Data from BPS shows fluctuations in the unemployment rate in Sukabumi City, with an increase in male unemployment from 2019 to 2021 and a decrease in female unemployment during the same period. COVID-19 has also contributed to the increase in unemployment due to restrictions on business and social activities. The Sukabumi City Manpower Office has undertaken various efforts, such as job training and job fairs, but has not been optimal in placing training participants into the workforce. The challenges faced include unclear information about job training and the lack of follow-up from the manpower office. This study provides suggestions and input for the Sukabumi City Manpower Office to improve efficiency in reducing the open unemployment rate through a more comprehensive and integrative approach.